Resistance training in asthma: clinical benefits, safety and implications for exercise prescription – a narrative review - Pszczółka, Agata; Matuszczak, Patryk; Kozak, Joanna; Bajor, Gabriela; Melka, Kacper; Szulewski, Mikołaj; Salagierska, Aleksandra; Machno, Patrycja; Jurczyk-Florkiewicz, Wiktoria; Gniadek , Zofia (Quality in Sport, 2026)
Background: Asthma is a chronic inflammatory airway disease that can limit exercise tolerance and promote physical deconditioning. While aerobic exercise is widely studied and recommended, resistance training remains under-investigated despite potential clinical benefits. Objective: This narrative review summarizes the rationale, physiological mechanisms, and clinical effects of resistance training in adults with asthma, with a focus on practical exercise prescription. Methods: Evidence from randomized controlled trials, systematic reviews, and observational studies addressing resistance, aerobic, and combined exercise interventions in adults with asthma was reviewed. Outcomes included asthma control, muscle strength, exercise capacity, and quality of life. Results: Resistance training improves muscle strength, functional capacity, and exercise tolerance, with a low risk of exercise-induced bronchoconstriction. Combined resistance and aerobic programs further enhance cardiorespiratory fitness, muscle function, and quality of life. Physiological mechanisms involve counteracting deconditioning, enhancing muscle mass, and modulating dyspnoea perception. Structured exercise programs with warm-up, progressive intensity, and symptom monitoring optimize safety and effectiveness. Conclusion: Resistance training is a safe and clinically relevant adjunct to aerobic exercise in asthma management, offering complementary benefits for physical function and quality of life. Further well-designed studies are needed to define optimal protocols, particularly for older adults and severe asthma populations.